Cerebral regional oxygen saturation during cardiopulmonary resuscitation and return of spontaneous circulation: A systematic review and meta-analysis. (February 2021) - Sanfilippo, Filippo; Murabito, Paolo; Messina, Antonio; Dezio, Veronica; Busalacchi, Diana; Ristagno, Giuseppe; Cecconi, Maurizio; Astuto, Marinella
Abstract: Aim: Predicting the return of spontaneous circulation (ROSC) during cardiopulmonary resuscitation in victims of cardiac arrest (CA) remains challenging. Cerebral regional oxygen saturation (rSO2) measured during resuscitation is feasible, and higher initial and overall values seem associated with ROSC. However, these observations were limited to the analysis of few small single-centre studies. There is a growing number of studies evaluating the role of cerebral rSO2 in the prediction of ROSC. Methods: We conducted an updated meta-analysis aimed at investigating the association of initial and overall values of cerebral rSO2 with ROSC after CA. We performed subgroups analyses according to the location of CA and conducted a secondary analysis according to the country where the study was conducted (resuscitation practice varies greatly for out-of-hospital CA). Results: We included 17 studies. Higher initial rSO2 values (11 studies, n = 2870, 16.6% achieved ROSC) were associated with ROSC: Mean Difference (MD) -11.54 [95%Confidence Interval (CI)-20.96, -2.12]; p = 0.02 (I 2  = 97%). The secondary analysis confirmed this finding when pooling together European and USA studies, but did not for Japanese studies (p = 0.06). One multi-centre Japanese study was an outlier with large influence on 95%CI. Higher overall rSO2 values during resuscitation (9 studies, n = 894, 33.7% achieving ROSC) were associated with ROSC: MD-10.38; [-13.73, -7.03]; p < 0.00001 (I 2  = 77%). All studies were conducted in Europe/USA. Conclusions: This updated meta-analysis confirmed the association between higher initial and overall values of cerebral rSO2 and ROSC after CA. However, we found geographical differences, since this association was not present when Japanese studies were analysed separately. Keywords: near infrared spectrometry; advanced cardiac life support; resuscitation order; cardiopulmonary resuscitation.